2019
DOI: 10.4269/ajtmh.18-0834
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mycobacterial Antigen–Induced Pro-Inflammatory Cytokine Production in Lymph Node Tuberculosis

Abstract: Lymph node tuberculosis (LNTB) is characterized by the enhanced baseline and antigen-specific production of type 1/17 cytokines and reduced baseline and antigen-specific production of interleukin (IL)-1β and IL-18 at the site of infection when compared with peripheral blood. However, the cytokine profile in the lymph nodes (LNs) of Mycobacterium tuberculosis culture-positive LNTB (LNTB+) and negative LNTB (LNTB−) has not been examined. To address this, we have examined the baseline and mycobacterial antigen-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…When stimulated with Mtb-specific antigens, CFU+ lymph nodes had higher interleukin-10 (IL-10), T helper type 1 (Th1), T helper type 17 (Th17), and granulocyte-macrophage colony-stimulating factor (GMCSF) protein levels compared to CFU-lymph nodes from TBLN patients. No difference in levels of Th2 cytokines (IL-4, IL-5, and IL-13), IL-1β, or IL-18 was observed [66]. In contrast to other studies, Rahman and colleagues [67] showed that lymph nodes from children with TBLN had lower interferon alpha (IFNα), TNF, and IL-17 expression compared to non-TB-specific reactive lymph nodes and healthy tonsil controls.…”
Section: Immune Response Of Lymph Nodes To Mtbmentioning
confidence: 89%
See 1 more Smart Citation
“…When stimulated with Mtb-specific antigens, CFU+ lymph nodes had higher interleukin-10 (IL-10), T helper type 1 (Th1), T helper type 17 (Th17), and granulocyte-macrophage colony-stimulating factor (GMCSF) protein levels compared to CFU-lymph nodes from TBLN patients. No difference in levels of Th2 cytokines (IL-4, IL-5, and IL-13), IL-1β, or IL-18 was observed [66]. In contrast to other studies, Rahman and colleagues [67] showed that lymph nodes from children with TBLN had lower interferon alpha (IFNα), TNF, and IL-17 expression compared to non-TB-specific reactive lymph nodes and healthy tonsil controls.…”
Section: Immune Response Of Lymph Nodes To Mtbmentioning
confidence: 89%
“…Human studies investigating the immune response in Mtb-infected lymph nodes compared biopsied cervical lymph nodes of patients with TBLN with either healthy controls, patients with only pulmonary TB, and patients with other lymph node disease (e.g., cancer, non-TB-specific reactive lymphadenitis) [64][65][66][67]. All studies obtained transcription profiles, but only one study examined protein levels.…”
Section: Immune Response Of Lymph Nodes To Mtbmentioning
confidence: 99%
“…We recruited lymph node TB culture-positive (hereafter LNTB+, n = 18) and lymph node TB culture-negative (hereafter LNTB-, n = 10) patients and performed the experiments. The demographics and hematological data of the study population were reported previously [8] and the same set of lymph node (LN) samples was used for this study. LNTB+ group was characterized based on the excision biopsy exhibiting positive for Mycobacterium tuberculosis (Mtb) on liquid cultures and LNTB-(culture grades 0 [no or <19 colonies]) group was characterized based on the negative results for Mtb detection in liquid cultures.…”
Section: Study Groupsmentioning
confidence: 99%
“…The LN cells from LNTB+ and LNTB-individuals were isolated, cultured and either unstimulated, stimulated with Mtb (PPD [Staten's Serum Institute], ESAT-6, CFP10 [BEI resources, PLOS ONE 10 μg/mL]), non-Mtb (HIV Gag PP, (AIDS Reagent Program, Division of AIDS, NIAID, NIH), 10 μg/mL) and positive control (phorbol myristate acetate/Ionomycin [P/I], (Calbiochem, San Diego, CA), 12.5 and 125 ng/mL) antigens [8,9]. Before culturing, the LNs were transported in the Roswell Park Memorial Institute (RPMI)-1640 medium (Gibco) after biopsy and washed two times in RPMI 1640 medium.…”
Section: Lymph Node Isolation Culture and Antigen Stimulationmentioning
confidence: 99%
See 1 more Smart Citation